Self-organised initiatives: a planners’ subversive tool for fragmented urban spaces - Moreno Pessôa, Igor Tempels (A+BE | Architecture and the Built Environment, 2019)
Self-organised initiatives are abundant in Brazil. Nevertheless, it is not clear how these informal, bottom-up and self-organised initiatives, supported by urban planners, are shaping the built environment. This chapter investigates whether these self-organised initiatives are able to undermine the underlying dynamics of spatial fragmentation in Brazilian metropolises by promoting social connections between groups that are extremely diverse. Since self-organised initiatives not only promote spatial connections but also social connections between different groups, the primary premise of this study is that they will have a positive impact on reducing the spatial fragmentation present in Brazilian metropolises. Therefore, the central question here is: To what extent can self-organised initiatives promote social connection in the public spaces of highly fragmented and unequal urban contexts? The analysis was based on data collected from 22 in-depth interviews with members of self-organised initiatives, experts as well as field observations during some actions of the initiatives. The interviews were conducted in Brasília, Rio de Janeiro and São Paulo during two months of fieldwork